Learner identities and the will to understand: The experiences of undergraduate biosciences students in the UK - McCune, Velda (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Understanding depends on applying a particular kind of effort to learning. The research reported in this article investigates what influences students’ willingness to engage in the kinds of active learning which would be required for a deep personal understanding of the “ways of thinking and practising” of their subject area. The analysis is based on 19 group interviews with 59 experienced biosciences students from three contrasting types of university in the UK, drawn from a more extensive set of transcripts from a large-scale national project. A rigorous thematic analysis of the data was carried out using HyperRESEARCH, a computer program which has the flexibility to allow thorough and diverse analyses of qualitative data. The findings illustrate the interplay between the will to understand, aspects of students’ identities and key dimensions of the contexts within which they were learning. Where interaction between the students and their learning context allowed for more authentic learning experiences, this seemed to have a positive influence on their willingness to engage actively and critically with their studies.